Screening of a Chemical Library by HT-G4-FID for Discovery of Selective G-quadruplex Binders - Largy, Eric; Saettel, Nicolas; Hamon, Florian; Dubruille, Sylvie; Teulade-Fichou, Marie-Paule (Current Pharmaceutical Design, 2012)
Due to the lack of structural guidelines about G-quadruplex ligands, rational design cannot be the only approach to discover potent G4-ligands. As a complementary approach, screening of chemical library may provide interesting scaffolds known as hits provided that specific tools are available. In this work, the Institut Curie-CNRS chemical library was firstly screened by chemoinformatics methods. Similarity estimations by comparison with reference compounds (Phen-DC3, 360A, MMQ12) provided a set of molecules, which were then evaluated by high-throughput G4-FID (HT-G4-FID) against various G-quadruplex DNA. A full investigation of the most interesting molecules, using the HT-G4-FID assay and molecular modeling, supplied an interesting structure-activity relationship confirming the efficiency of this general approach. Overall, we demonstrated that HT-G4-FID coupled with screening of chemical libraries is a powerful tool to identify new G4-DNA binding scaffolds.
Keywords: fluorescence